Comparison of stroke recognition and stroke severity scores for stroke detection in a single cohort. Issue 9 (2nd December 2014) - Purrucker, Jan C; Hametner, Christian; Engelbrecht, Andreas; Bruckner, Thomas; Popp, Erik; Poli, Sven
Abstract : Objective: First, to determine the sensitivity and specificity of six stroke recognition scores in a single cohort to improve interscore comparability. Second, to test four stroke severity scores repurposed to recognise stroke in parallel. Methods: Of 9154 emergency runs, 689 consecutive cases of preclinically 'suspected central nervous system disorder' admitted to the emergency room (ER) of the Heidelberg University Hospital were included in the validation cohort. Using data abstracted from the neurological ER medical reports, retrospective assessment of stroke recognition scores became possible for the Cincinnati Prehospital Stroke Scale (CPSS), Face Arm Speech Test (FAST), Los Angeles Prehospital Stroke Screen (LAPSS), Melbourne Ambulance Stroke Screen (MASS), Medic Prehospital Assessment for Code Stroke (Med PACS) and Recognition of Stroke in the Emergency Room score (ROSIER), and that of stroke severity scores became possible for the Kurashiki Prehospital Stroke Scale (KPSS), Los Angeles Motor Scale (LAMS) and shortened National Institutes of Health Stroke Scale (sNIHSS)-8/sNIHSS-5. Test characteristics were calculated using the hospital discharge diagnosis as the reference standard. Results: The CPSS and FAST had a sensitivity of 83% (95% CI 76 to 88) and 85% (78% to 90%) and a specificity of 69% (64% to 73%) and 68% (63% to 72%), respectively. The more complex LAPSS, MASS and Med PACS had a high specificity (92% to 98%) but low sensitivity (44% to 71%). In the ROSIER, sensitivity (80%, 73 to 85) and specificity (79%, 75 to 83) were similar. Test characteristics for KPSS, sNIHSS-8 and sNIHSS-5 were similar to the simple recognition scores (sensitivity 83% to 86%, specificity 60% to 69%). The LAMS offered only low sensitivity. Conclusions: The simple CPSS and FAST scores provide good sensitivity for stroke recognition. More complex scores do not result in better diagnostic performance. Stroke severity scores can be repurposed to recognise stroke at the same time because test characteristics are comparable with pure stroke recognition scores. Particular shortcomings of the individual scores are discussed.